L03 Use and impact of neuroleptics in Huntington's disease: a prospective cohort study of the Huntington French speaking group. (16th November 2010) - Dolbeau, G; Lombard, A; Youssov, K; Dürr, A; Charles, P; Verny, C; Azulay, J-P; Krystkowiak, P; Simonin, C; Tranchant, C; Goizet, C; Damier, P; et al.
Abstract : Background: Recent reviews of available drug trials and case reports conclude that the guidelines for the treatment of Huntington's disease (HD) symptoms are scarce. Aims: We wanted to better understand the use of neuroleptics and related drugs (NL-R) in HD by observing their use in clinical practice and their impact on disease progression. Methods/techniques: We explored and compared the profile and evolution of patients treated by NL-R in the cohort of the Huntington French Speaking Group Cohort. This cohort comparative study included 760 patients with available CAG repeats and medication information, followed for 22.4 (±23.3) months between 2002 and 2010. Results/outcome: 63% of patients were treated by a NL-R at least once during the follow up. The main NL-R used by the clinicians were (before and after 2006, respectively): olanzapine (38.8 vs 34.5%, NS), risperidone (15.2 vs 16.0%, NS), tiapride (9.4 vs 8.5%, NS) and tetrabenazine (0.8 vs 18.9%, p<0.001). Profiles differed by chorea (p<0.05), UHDRS Functional Assessment Scale (FAS), Total Functional Capacity (TFC) (p<0.05) and Independence Scale (IS) (p<0.01), with patients taking olanzapine being less disabled on the functional scales. Conversely, tiapride was provided to the most advanced patients. The risperidone group displayed the lowest chorea score (8.4±5.4). During treatment, effectiveness adjusted for baseline profile was statistically different between NL-R. Changes in clinical evolution differed for TFC and FAS (p<0.05) and for body mass index (BMI) (p<0.001). Patients under tiapride displayed the slower functional decline and patients with tetrabenazine were the only one where BMI decreased (3.4±5.7%/year). Conclusion: In our cohort study of 760 HD patients, the four main NL-R used in HD (olanzapine, risperidone, tiapride and tetrabenazine) seem to have different effectiveness on the progression of the disease.